How the population’s perceptions influence their behaviours regarding the consumption of fibre rich foods - Martinho, CAC (2012)
The association between dietary fibre, health benefits and healthy food has been studied in recent years. The food industry, to accompany the strong interest shown by consumers, has placed at their disposal new products, rich in dietary fibre. In order to meet this huge interest and demand for these products, this work was elaborated, which had as main objective to evaluate the degree of knowledge of the Portuguese population about fibre and its effects on health, as well as evaluating the their consumption habits in respect of fibres. To achieve this goal an inquiry was carried out by questionnaire to 182 adults. The most relevant results indicate that only 13% of the inquired eat two meals a day with vegetables and/or salads and 9% eat at least 3 pieces of fruit. Whole grains are never consumed by 41% and 18% do so at least once a week. The vast majority (90%) of respondents have the notion that fibre intake contributes to the prevention and treatment of diseases. With this work it was concluded that respondents‘ knowledge about dietary fibre is insufficient, and that although they give great importance to their role in treatment and prevention of diseases, the level of intake is too low.